Efficient use of rice residues. - NICOLAS, Jose S. (1995)
Discusses end-use capabilities of rice by-products utilized at the grassroots level in the Philippines. Notes that the crop residues largely found their way into three major destination channels : agriculture or acquculture, industry, and household.